Scepter of memories - Ortega, Claribel A. (Ortega, Claribel A. Witchlings (Series), 2025)
Seven, Thorn, and Valley are determined to stop Ambert Lophiifor's plan of taking over the Twelve Towns. With Seven's Uncle powers and their new coven behind them, surely they'll be able to defeat him at last. But strange things are happening around Ravenskill--the Witchlings' allies are starting to forget them! When the Witchlings are charged with the crime of practicing unnatural and dangerous magic, no one is there to come to their defense. Without any support, the Witchlings are forced to flee beyond the borders of the Twelve Towns and into the swirling grey mists of the Enchanted Grim, hoping to find the one witch who might have the knowledge and power to help them: Delphinium Larkspur. The Grim is an uncharted wilderness filled with monstruos, where no normal witch would ever be able to survive. But there's nothing normal about the Witchlings, their courage, or their friendship. Together with their Nightbeasts, they are determined to find a way to save their home. Even if it means embracing the monstruos within themselves.